Circadian rhythm of plasminogen activator inhibitor-1 and cardiovascular complications in type 2 diabetes - Yu, Yongzhuo; Li, Wenxuan; Xu, Lili; Wang, Yangang (Frontiers in Endocrinology, 2023)
Cardiovascular complications are a common death cause in type 2 diabetes patients, as they are often combined. Plasminogen-activator Inhibitor 1 (PAI-1) participates in the development and progression of cardiovascular complications in diabetes. Insulin resistance increases PAI-1 production, and high PAI-1 levels lead to an environment conducive to thrombosis and earlier and more severe vascular disease. Current evidence also suggests that PAI-1 has a rhythmic profile of circadian fluctuations and acrophase in the morning within a single day, which might explain the high morning incidence of cardiovascular events. Thus, PAI-1 is a possible drug target. Although several PAI-1 inhibitors have been developed, none have yet been allowed for clinical use. Research on rhythm has also led to the concept of “chronotherapy”, a rhythm-based drug regimen expected to improve the treatment of cardiovascular complications in diabetic patients. Herein, we searched several databases and reviewed relevant articles to describe the circadian rhythm characteristics and endogenous molecular mechanisms of PAI-1, its relationship with insulin resistance, the causes of cardiovascular complications caused by PAI-1, and the current development of PAI-1 inhibitors. We also summarized the possibility of using the circadian rhythm of PAI-1 to treat cardiovascular complications in diabetic patients.